The western experts assessment of sanctions against Russia (Халықаралық қатынастар және халықаралық құқық сериясы, 2016)
Beginning of 2014 is marked by the fact that the US and the EU imposed sanctions against Russia after the annexation of the Crimea by the Russian Federation. Taking into account the fact that the sanctions entail serious consequences for their economies, it was decided to introduce restrictive measures step by step depending on the change of Russian behavior. The first step of sanctions is characterized by visa bans and the freezing of assets in the United States. The second phase consists of two stages, where the restrictive measures concerned visa issues and the cessation of new investment. In the third stage, the US imposed trade restrictions, as well as financial sanctions, the energy sector, the defense sector were included to the sanctions, Russia also expects a limited market access of US debt. In the article, the authors analyzed the impact of sanctions on the economies of European countries, examined the effectiveness and potential impact of sanctions and the views of leading American and European experts opponents were presented.